THEORETICAL AND METHODOLOGICAL FOUNDATIONS AND HISTORICAL DEVELOPMENT OF THE HANDLING OF APPEALS IN NATIONAL HUMAN RIGHTS INSTITUTIONS (World Bulletin of Social Sciences, 2024)
The article shows the stages of development of citizens' right to appeal in the Republic of Uzbekistan, information about national human rights institutions and their powers to consider appeals, the legal status and development of national institutions, an analysis of the work carried out by the National Center of the Republic of Uzbekistan for Human Rights in the field of appeals in 2023